FAKTOR –FAKTOR YANG MEMPENGARUHI PERUBAHAN PERILAKU PETERNAK TERHADAP PENGOBATAN DAN PENCEGAHAN NEMATODIASIS PADA KAMBING - Supriyanto; Nurdayati; Ahadiati N (Politeknik Pembangunan Pertanian Manokwari, 2016)
The study was conducted at the Japan District of Magelang regency Tegalrejo time execution of activities in April through June 2016, with the objective to be achieved is to know the level and the factors - factors that influence changes in the behavior of farmers. Samples were taken census of members of Farmers Group